Antibiotic activity of Plectranthus ornatus Codd., a Traditional Medicinal Plant - NASCIMENTO,FERNANDA R. (2017)
ABSTRACT The dichloromethane extract of Plectranthus ornatus Codd., a tradicional medicinal plant, showed antibiotic activity with minimum inhibitory concentration (MIC) values of 0.4 mg.mL-1 and 100 percent of biofilm inhibition against Staphylococcus aureus strains isolated from animals with mastitis infections. Based on these antibacterial activities, in addition to ethnopharmacological reports from healing men and farmers in Brazil, an herbal soap was produced from this active extract and was tested both in vitro and in vivo. In vivo assays conducted on these herbal soaps led to results similar to those previously conducted with the active extract. These results indicated the great potential of this plant for use as an excipient by preparing herbal antibacterial soaps as an alternative veterinary medicine aimed at controlling bovine mastitis infections on small Brazilian farms.